Neurological disorders in HIV: Hope despite challenges. Issue 3 (10th February 2022) - Uwishema, Olivier; Ayoub, Georges; Badri, Rawa; Onyeaka, Helen; Berjaoui, Christin; Karabulut, Ece; Anis, Heeba; Sammour, Christophe; Mohammed Yagoub, Fatima E. A.; Chalhoub, Elie
Abstract: Introduction: Human Immunodeficiency virus (HIV) is a virus that causes several diseases by attacking the human immune system. It is transmitted by contact with certain bodily fluids of an infected person, most commonly during unprotected sex, through sharing needles, or from mother to baby during pregnancy, birth or breastfeeding. The central nervous system is not spared from this virus, as HIV has been shown to induce several neurological disorders. However most neurological pathologies (such as dementia, infections, meningitis, and neuropathy) rarely show until late stages, in this case, after the patients develop acquired immunodeficiency syndrome (AIDS). This article aims to review the neurological disorders in the HIV population and the attempts initiated to limit the disease. Methodology: Data were collected from medical journals published on PubMed, Ovid MEDLINE, Science Direct and Embase bibliographical databases with a predefined search strategy. All articles considering neurological disorders associated with HIV were considered. Results: To date, the pathogenesis of HIV‐associated neurological complications remains poorly elucidated; thus, imposing a hindrance and limitations on the treatment options. Nevertheless, some studies have reported alterations in dendritic spine as the causative agent for developing brain damage. Conclusion: HIV remains one of the most serious global health challenges, with neurological manifestations imposing a major concern among patients with HIV. Despite the availability and efficacy of antiretroviral therapies, yet, the risk of developing neurological complications remains relatively high among patients with HIV. Thus, the 2030 HIV vision must focus on further preventive measures to protect HIV patients from developing such neurological complications.